The «Summa Halensis»: tradition and renewal about the problem of beauty - Costarelli Brandi, Hugo Emilio (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
One of the topics that the metaphysics of the Thirteenth Century studied with particular originality was the modes of the being, such as unity, truth and good, which exceed the limits set by the categories. However, the beauty did not have the intellectual prominence of the others, mostly because it was always presented in relation to the good, and then do not find a place of its own. The Summa written by Alexander of Hales and his disciples, provides a new reading of the tradition and gives to the pulchrum a particular status, enabling new speculative developments.